Ginsenosides Regulates Innate Immunity to Affect Immune Microenvironment of AIH Through Hippo-YAP/TAZ Signaling Pathway - Zhang, Kehui; Li, Jiacheng; Shi, Zhe; Zhu, Yingying; Yang, Jing; Liu, Xiaolin; Que, Renye; Lin, Liubing; Chen, Yirong; Li, Yong (Frontiers in Immunology, 2022)
Autoimmune hepatitis (AIH) is characterized by chronic progressive liver inflammatory, but there is still no safe and effective medicine. Therefore, glucocorticoid remains the top choice for AIH treatment. In previous studies, it has been confirmed that ginsenosides (GSS) can produce glucocorticoid-like effects and therapeutic effects on various autoimmune diseases. However, the mechanism of GSS for AIH remains unclear. As an important part of the innate immune system, bone marrow-derived suppressor cells (MDSC) have been identified as an important driver of follow-up acquired immune response in many autoimmune diseases, including AIH. Herein, it was found out that GSS intervention can be effective in regulating the immune microenvironment and liver impairment induced by Con A in AIH mice. In vitro, the MDSCs derived from healthy mice and the T cells deried from AIH mice were co-cultured. Then, different drugs were intervened with to explore the therapeutic mechanism. Besides, the proliferation and differentiation of MDSCs and T cells were analyzed by flow cytometry, while GR, Hippo-YAP signal pathway and the expression of MDSC-related genes and proteins were detected through qRT-PCR and Western Blot. The changes in NO and ROS levels were further analyzed. The trend of related cytokines expression (IFN- γ, TGF- β, IL-10, IL-6, IL-17) was detected by ELISA. Furthermore, an analysis was conducted as to the ALT and liver pathology of mice for evaluating the liver function of mice. It was discovered that MDSCs proliferation was inhibited, and that T cells tended to differentiate into Th17 rather than Treg in AIH mice. Moreover, the intervention of GSS activated GR and Yap, in addition to promoting the proliferation of MDSCs, especially M-MDSCs. This further promoted the differentiation of Treg to enable immune tolerance, thus alleviating liver impairment. Therefore, it was proposed that GSS can alleviate AIH by modulating the innate immunity and adaptive T cell immunity, which may be the underlying mechanism for GSS to mitigate the liver impairment induced by AIH.